Prevalence of periodontal disease in pregnant women - Singh, Neelam; Verma, Urvashi; Yadav, Poonam; Nigam, Asha; Arora, Shikha; Singh, Alok; Singh, Rashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Periodontitis is inflammation of the periodontium that extends beyond the gingiva and produces destruction of the connective tissue attachment of the teeth. Maternal oral health is very important factor in determining pregnancy outcome not only for the mother but also for the health of fetus. Various forms of periodontal infections have been correlated to adverse pregnancy outcomes as miscarriage, preterm birth, preeclampsia, preterm birth, low birth weight, IUGR, still birth. Good maternal oral health may be key to childhood caries prevention. Methods: Two hundred and sixty-three pregnant women were included as per inclusion criteria. Written informed consent of the eligible women was taken. Subjects were evaluated on the basis of predesigned and pretested study proforma with respect to history, clinical examination and ultrasonography. Oral health examination of the patients was conducted at the time of inclusion into study and re-examined in the postpartum period for maternal and perinatal outcomes. Results: Prevalence of periodontal disease was seen in 77.18% of pregnant women. There was no statistically significant association between periodontal disease and maternal co-morbidities like GDM, Pre-eclampsia and gestation age of delivery. Significant correlation was found between periodontal disease and socio-economic status of the patients. There was significant correlation between birth weight and periodontal disease. Conclusions: Periodontal disease is prevalent in pregnancy. Pregnant women were not aware regarding the role of periodontal disease in adverse pregnancy outcomes and the importance of regular dental check-up.